Effects of plant growth-promoting rhizobacteria on blueberry growth and rhizosphere soil microenvironment - Mengjiao Wang; Xinlong Yang (PeerJ, 2024)
Background Plant growth-promoting rhizobacteria (PGPR) have a specific symbiotic relationship with plants and rhizosphere soil. The purpose of this study was to evaluate the effects of PGPR on blueberry plant growth, rhizospheric soil nutrients and the microbial community. Methods In this study, nine PGPR strains, belonging to the genera Pseudomonas and Buttiauxella, were selected and added into the soil in which the blueberry cuttings were planted. All the physiological indexes of the cuttings and all rhizospheric soil element contents were determined on day 6 after the quartic root irrigation experiments were completed. The microbial diversity in the soil was determined using high-throughput amplicon sequencing technology. The correlations between phosphorus solubilization, the auxin production of PGPR strains, and the physiological indexes of blueberry plants, and the correlation between rhizospheric microbial diversity and soil element contents were determined using the Pearson’s correlation, Kendall’s tau correlation and Spearman’s rank correlation analysis methods. Results The branch number, leaf number, chlorophyllcontentand plant height of the treated blueberry group were significantly higher than those of the control group. The rhizospheric soil element contents also increased after PGPR root irrigation. The rhizospheric microbial community structure changed significantly under the PGPR of root irrigation. The dominant phyla, except Actinomycetota, in the soil samples had the greatest correlation with phosphorus solubilization and the auxin production of PGPR strains. The branch number, leaf number, and chlorophyllcontent had a positive correlation with the phosphorus solubilization and auxin production of PGPR strains and soil element contents. In conclusion, plant growth could be promoted by the root irrigation of PGPR to improve rhizospheric soil nutrients and the microenvironment, with modification of the rhizospheric soil microbial community. Discussion Plant growth could be promoted by the root irrigation of PGPR to improve rhizospheric soil nutrients and the microenvironment, with the modification of the rhizospheric soil microbial community. These data may help us to better understand the positive effects of PGPR on blueberry growth and the rhizosphere soil microenvironment, as well as provide a research basis for the subsequent development of a rhizosphere-promoting microbial fertilizer.